Analysis of Professional Training of Indian Forest Service Officers - Pandey, Gopa (Indian Forester, 2013)
The training of Indian Forest Service officers at Indira Gandhi National Forest Academy, Dehradun is reviewed in the light of the current job requirements of the IFS officers. The training components, design and duration are discussed to reflect upon the weightage assigned to each activity during 24 months of professional training at IGNFA. The emphasis on physical fitness and indoor vs. outdoor activities finds a mention as the personality development of forest officers depends heavily on tours, exercises and excursions. The inputs provide an exposure to various silvicultural systems in India which goes a long way in carving out professional discharge of their duties. The analysis concludes that forestry is not merely a profession, but is also a way of life, the traits of which are inculcated during the professional forestry training at IGNFA. Other in-service training programmes introduced by the Government of India ensure personnel development in the right direction during the progression of their career.